The Impact of the Coronavirus on Argentine Presidential Standing - Klobovs, Lucas (Revista Latinoamericana de Opinión Pública, 2021)
When Alberto Fernández the presidency in December 2019 and the debate on whether his leadership was eclipsed by the presence of the vice president Cristina Kirchner had already begun. In this context, the coronavirus spreads throughout Argentina and the president achieves high levels of approval (even above those achieved after assuming the office) as long as social concerns about the pandemic were increasing. What is the real impact of coronavirus on the president?s figure? At once, this increased appraisal of his job performance triggers the consolidation of his authority but, at the same time, generates the question mark as to whether this consolidation is real or temporary.